Increasing physical activity of children during school recess. Issue 3 (29th June 2015) - Hayes, Lynda B.; Van Camp, Carole M.
<x xml:space="preserve">Abstract</x> Physical activity is crucial for children's health. Fitbit accelerometers were used to measure steps of 6 elementary students during recess. The intervention included reinforcement, self‐monitoring, goal setting, and feedback. Steps taken during the intervention phase (M = 1, 956 steps) were 47% higher than in baseline (M = 1, 326 steps), and the percentage of recess spent in moderate‐to‐vigorous physical activity was higher during intervention (M = 25%) than in baseline (M = 4%). These methods successfully increased steps during recess and could be used to increase steps in other settings.